PENDAMPINGAN MANAJEMEN DAN PENGEMBANGAN USAHA KULINER DONATE GENDHIS MANIS - Marmono Singgih; Ema Desia Prajitiasari; Kristian Suhartadi Widi Nugraha (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The declining national economic conditions as a result of the Covid-19 pandemic were felt directly by the community, especially MSMEs engaged in the food and beverage sector. However, the stagnation and slowdown of the economy due to the pandemic cannot be left alone. The massive vaccination movement and the culture of health procedures in the community gave rise to a new spirit to re-open a business. Donate Gendhis Manis is one of the culinary businesses that developed during the Covid-19 pandemic. Challenges faced are limited insight and experience in business management in terms of production, marketing, human resources, finance, and risk management. The community service team tries to help develop the business by brainstorming, FGD, simulation, and providing production tools. As a result, Donate Gendhis Manis' culinary industry can empower itself by being more sensitive to market trends, environmental changes, and consumer tastes and improving its appearance by redesigning its packaging